Analisis dan Perancangan Aplikasi Fathforce Starter Kit Pro di PT. Inovasi Media Menggunakan Framework Laravel - Niqotaini, Zatin; Yulistiawan, Bambang Saras; Gusti, Kharisma Wiati; Zaidiah, Ati; Yoga, Titan Parama (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
Today's technological advances are inseparable from the role of applications, which are software that combines certain functions and can be downloaded by users. Abundant app services are available in the Apple Store for iPhone and Play Store for Android. PT Inovasi Media, a Professional Website Development Services company, needs an application that can facilitate website development. Using Laravel's built-in Starter Framework, the company seeks to develop a Starter Framework specifically for website development, which is open source so that it can be accessed and modified by many people. The research stages involve Literature Study, Observation, Interviews, Data Collection, Design, Implementation, and Evaluation. Application design is done using UML (Unified Modelling Language) as well as user interface. Overall, the web app is open source, giving access and modification capabilities to anyone who needs it.